Activation of M2 muscarinic acetylcholine receptors by a hybrid agonist enhances cytotoxic effects in GB7 glioblastoma cancer stem cells. (September 2018) - Cristofaro, Ilaria; Spinello, Zaira; Matera, Carlo; Fiore, Mario; Conti, Luciano; De Amici, Marco; Dallanoce, Clelia; Tata, Ada Maria
Abstract: In previous studies, we found that the orthosteric muscarinic agonist arecaidine propargyl ester (APE) (100 μM) induced a decreased cell proliferation and severe apoptosis in glioblastoma cancer stem cells (GSCs). In this report, we have investigated the effects mediated by hybrid (orthosteric/allosteric) muscarinic agonists P-6-Iper and N-8-Iper on GSCs survival. At variance with APE, the agonist N-8-Iper inhibited cell growth in a dose dependent manner and also impaired cell survival at low doses. The inhibitory effects of the N-8-Iper action appear to be mediated by M2 receptor activation, since they were strongly reduced by co-administration of the selective M2 receptor antagonist methoctramine as well as upon M2 receptor silencing. Moreover, analysis of the expression of phosphorylated histone H2AX (γ-H2AX) indicated that the treatment with N-8-Iper produced a decreased cell survival by induction of DNA damage. The ability of N-8-Iper to produce a cytotoxic effect and apoptosis at low doses indicates that this muscarinic agonist is a suitable probe in a putative therapeutic intervention on glioblastoma through M2 receptor activation. Graphical abstract: Highlights: Dualsteric muscarinic agonist N-8-Iper showed cytotoxic effects in GSCs. N-8-Iper inhibited cell growth in a dose dependent manner and caused a decreased cell survival by induction of DNA damage. The effects of N-8-Iper are mediated by M2 receptor activation. M2 activators result promising therapeutic agents for glioblastoma therapy.